The nature of thermochromic effects in dyeings with indigo, 6-bromoindigo, and 6, 6′-dibromoindigo, components of Tyrian purple. (June 2015) - Ramig, Keith; Lavinda, Olga; Szalda, David J.; Mironova, Irina; Karimi, Sasan; Pozzi, Federica; Shah, Nilam; Samson, Jacopo; Ajiki, Hiroko; Massa, Lou; Mantzouris, Dimitrios; Karapanagiotis, Ioannis; et al.
Abstract: Thirteen fabrics are each dyed with either indigo, or 6-bromoindigo, or 6, 6′-dibromoindigo. When the dyed fabrics, which had not undergone any finishing procedures, are boiled in water for 10 min, color changes are observed: many indigo- and 6-bromoindigo-dyed fabrics turn more blue, while many 6, 6′-dibromoindigo-dyed fabrics turn more red. These color changes are characterized by reflectance spectra and colorimetry data. Evidence is presented that the color changes are related to particle sizes of the dyes: 6, 6′-dibromoindigo-dyed carbon nanotubes, used as a fabric surrogate, show an increase in dye-particle size upon heating, as judged by electron microscopy. Because we have shown previously that 6-bromoindigo-dyed carbon nanotubes give decreased dye-particle size when heated, we infer that, no matter the indigoid or fabric, smaller particles tend to cause a bluer fabric shade, while larger particles cause a redder shade. Highlights: Thermochromic effects seen in indigoid dyeings are explained. Indigo- and 6-bromoindigo-dyed fabrics turn blue upon heating. 6, 6′-Dibromoindigo-dyed fabrics turn red upon heating. Electron microscopic analysis of dyed carbon nanotubes shows changes in dye-particle size with heat. The opposing thermochromic effects coincide with changes in dye-particle size.